Means of visualization in teaching Ukrainian as a foreign language to modern students with clip way of thinking - Kushnir, I.; Zozulia, I.; Hrytsenko, O.; Uvarova, T.; Kosenko, I.; Гриценко, Ольга Вікторівна (My University, 2021)
The purpose of the research is to prove the effectiveness of the use of visualization in the process of teaching Ukrainian as a foreign language to students with clip way of thinking. The following methods have been used, namely: analysis, synthesis, comparison, systematization and generalization of scientific literature; testing and surveys; pedagogical experiment; quantitative and qualitative analysis of data, interpretation and generalization of the research results. The essence of visualization means has been revealed; the expediency of their use in the methodology of teaching foreign students the Ukrainian language has been substantiated. It has been proven that the role of Ukrainian teachers lies in considering all new trends in teaching, integrating computer perception of information by foreign students into teaching technology and using cognitive visualization in order to intensify the learning process
Keywords: Visualization. Ukrainian as a foreign language; Educational activities; Clip way of thinking